Mapping polarons in polymer FETs by charge modulation microscopy in the mid-infrared - Chin, Xin Yu (2014)
We implemented spatial mapping of charge carrier density in the channel of a conventional polymer Field-Effect Transistor (FET) by mid-infrared Charge Modulation Spectroscopy (CMS). CMS spectra are recorded with a high sensitivity confocal Fourier Transform Infra-Red (FTIR) microscope by probing electroinduced Infra-Red Active Vibrational (IRAV) modes and low-energy polaron bands in the spectral region 680–4000 cm−1. Thanks to the high specificity and strong oscillator strength of these modes, charge-induced reflectance measurements allow quantitative estimation of charge carrier densities within the FET channel, without the need for amplitude or phase modulation. This is illustrated by identifying the contribution of intrinsic and electrostatically induced polarons to conduction, and by mapping the polaron spatial distribution in a P3HT (Poly(3-hexylthiophene-2,5-diyl)) FET channel under different drain-source bias conditions. This work demonstrates the potential of mid-infrared charge modulation microscopy to characterize carrier injection and transport in semiconducting polymer materials.